2001
DOI: 10.1038/modpathol.3880361
|View full text |Cite
|
Sign up to set email alerts
|

Collecting-Duct Carcinoma of the Kidney with Prominent Signet Ring Cell Features

Abstract: We report a case in a 74-year-old woman of collecting-duct carcinoma of the kidney with prominent signet ring cell features. Grossly, the tumor measured 5.5 cm in greatest dimension, occupied the entire upper pole of the kidney, and was well circumscribed. Microscopically, it displayed a predominant tubulopapillary pattern of growth with a hyalinizing stroma. The tumor tubules were lined by a single layer of cells with large, pleomorphic nuclei, some of which had a hobnail appearance. Large intracytoplasmic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
1
8
1
2
Order By: Relevance
“…Cancer cell have positive expressions of CK (AE1/AE3), CK7, CK19, EMA, vimentin, CK34BE12, PNA and ulex europeus agglutinin (UEA), and negative expression of CD10 and CK20. Combination of CK34BE12 and PNA is able to detect 90% of CDC [24]. The results from pathological and immunohistochemical examinations are the important basis for the diagnosis of CDC and for differentiating it from other types of kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell have positive expressions of CK (AE1/AE3), CK7, CK19, EMA, vimentin, CK34BE12, PNA and ulex europeus agglutinin (UEA), and negative expression of CD10 and CK20. Combination of CK34BE12 and PNA is able to detect 90% of CDC [24]. The results from pathological and immunohistochemical examinations are the important basis for the diagnosis of CDC and for differentiating it from other types of kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Positive immunohistochemical staining for CK19, CK7, 34βE12 and vimentin has been previously reported to support the diagnosis of CDC (17). In addition, a previous study demonstrated that the CDC cells also express EMA, peanut lectin agglutinin and Ulex europaeus agglutinin 1 (18). In the present study, immunohistochemical analysis demonstrated that the tumor cells were strongly positive for EMA and CK7, while they reacted focally with vimentin.…”
supporting
confidence: 51%
“…Breast [3] Large bowel [4] Appendix [5] Bladder, ureter, and pelvis [6] Ampulla of Vater [7] Esophagus [8] Prostate [9] Lung [10] Salivary glands [11] Sinonasal tract [12] Uterine cervix [13] Uterine corpus [14] Ovary (questionable) [15] Other neoplastic conditions Malignant lymphoma [16] Malignant melanoma [17] Basal cell carcinoma of skin [18] Squamous cell carcinoma of skin [19] Stromal tumor of ovary [20] Chondrosarcoma [21] Ependymoma [22] Malignant mesothelioma [23] Meningioma [24] Collecting duct carcinoma of kidney [25] Urothelial carcinoma of renal pelvis with collagenous spherulosis [26] Follicular adenoma and carcinoma of thyroid [27] Salivary gland adenoma [28] Pituitary adenoma [29] Carcinoid tumor of gallbladder [30] Pancreatic endocrine neoplasm [31] GIST [32] Peutz-Jeghers polyps [33] Epithelioid leiomyoma [34] Gastric schwannoma [35] Testicular seminoma [36] Nonneoplastic conditions Inflammatory/necrotizing conditions of gastrointestinal tract and gallbladder [33,[37][38][39][40][41][42][43]…”
Section: Casementioning
confidence: 99%